A study of alternative techniques to mercury amalgamation for gold extraction in artisanal and small-scale gold mining - Manzila, Archippe Ngwey (Department of Chemical Engineering, 2023)
Artisanal and small-scale gold mining (ASGM) has many definitions depending on the context. However, the common theme that characterises gold mining operations that fall within this category is that they make use of rudimentary methods to mine and process gold. The ASGM sector is a source of livelihood for millions of people worldwide and continues to grow due to the ever-rising demand for gold, and high unemployment rates which have been exacerbated by the Covid-19 pandemic, particularly in developing countries. Mercury amalgamation is the method of choice to recover gold in ASGM. This method consists of contacting the gold found within an ore with mercury to form an alloy i.e., the mercury-gold amalgam and subsequently burning off mercury to recover the gold in a form known as sponge gold. The popularity of this method has to do with its simplicity of application, low cost, and quick returns. However, mercury is a highly toxic substance; therefore, its use presents serious health risks for artisanal miners and their communities, and environmental risks for the ecosystems surrounding their operations. These risks arise primarily from the amalgam burning stage, whereby mercury is vapourised, and the dumping of mercury-rich tailings into local rivers. This mercury release affects human health by causing serious diseases that may lead to death. From an environmental perspective, mercury has been reported to severely pollute river ecosystems, inevitably finding its way to food chains. Due to these issues, alternative technologies such as borax smelting, the Gemini table, thiosulphate, cyanide, chlorine, and urea leaching, to name a few, have been developed or adapted over the years to substitute mercury. However, most of these technologies have not been successfully implemented in artisanal mining operations. This lack of success is primarily due to their complexity and high cost, making them unattractive to artisanal miners. This study investigates the application of cyanide and thiosulphate leaching as alternatives to mercury amalgamation for the recovery of gold in ASGM operations. Although cyanidation is practiced in ASGM, in some regions, it is only employed to treat tailings from the mercury amalgamation process. This is undesirable due to the fact that exposing mercury to cyanide results in the mobilisation of elemental mercury found in the tailings as mercury cyanide. This project investigates gold extractions that can be achieved with cyanide and alkaline thiosulphate systems and compares the results to those of mercury amalgamation. This investigation was undertaken by conducting leach experiments using cyanide at 1 g/L, 3 g/L and 5 g/L, and ammonium thiosulphate at 0.1 M and 0.5 M, on 3 ore samples originating from artisanal mining locations. The experiments were conducted using batch stirred tanks reactors and the operating conditions (T= 26°C, solids loading: 30%, particle size: --300 +150 µm) were selected to mimic as closely as possible the conditions of artisanal mining processes. The findings of the study revealed that cyanide leaching was the better performing technology compared to thiosulphate leaching as it achieved gold extractions of 71.6%, 69.7% and 67.8% for the 3 ores samples (Sample 1, Sample 2, and Sample 3, respectively) while thiosulphate leaching achieved gold extractions of 54.1%, 35.6% and 38.0% for the 3 ores, respectively. Studying the minerology of the ores, using XRF, XRD, QEMSCAN, SEM-EDS and diagnostic leach, revealed the presence of sulphide minerals hosting refractory gold which contributed to the low gold extractions observed. Cyanide leaching proved to be a system that is easier to control compared to thiosulphate leaching, making it much more attractive to artisanal miners. It is recognised that cyanide is a toxic chemical, however, the method is already practiced in ASGM and cannot be simply wished away. Instead, steps must be taken for its safe and responsible use. Hence, this research makes recommendations on avenues that can be explored to reduce the risks associated with cyanide use. It was also found that cyanide leaching outperformed mercury amalgamation which typically achieves gold recoveries of 30-50%. Thiosulphate leaching may be capable of achieving better gold recoveries than mercury amalgamation as well, as one of the ore samples achieved a gold extraction of 54.1%. However, this would depend on the ore type and reagent conditions as it was found that the 3 ore samples responded differently to leaching.